Latest Strategies Promoting Stable and Efficient Perovskite, Organic, and Perovskite‐Organic Tandem Solar Cells - Hongrui Zhang; Yongmin Luo; Dr Top Archie Dela Peña; Dr Ruijie Ma; Prof He Yan; Prof Mingjie Li; Prof Mahesh Suryawanshi; Prof Jiaying Wu; Prof Ashraf Uddin (Advanced Materials Interfaces, 2025)
Abstract Developing solution‐processable photovoltaic materials is expected to foster cheaper solar cell technology through high‐throughput printing‐based fabrications. In recent years, solution‐based organic solar cells (OSCs) and perovskite solar cells (PSCs) have demonstrated great potential. However, achieving reliable stability and commercially competitive device efficiency remains a great challenge. Specifically, although Sn‐based narrow bandgap perovskites have shown significant advancements, the stability development for wide bandgap perovskites remains more promising, indicating its advantage for UV applications. Meanwhile, OSCs have made good progress in catching up with the PSC's device efficiency. However, most organic photoabsorbers demonstrate intrinsic photo‐degradation from UV exposure while having excellent stability for near‐infrared (NIR) applications. Imperatively, constructing perovskite‐organic tandems is anticipated to bear synergistic benefits for long‐term operation stability, in addition to higher device efficiency. On the other hand, this notion remains primarily theoretical. Accordingly, there is a rapid evolution of material designs and device engineering strategies, extending the limits of both organic and perovskite absorbers. Likewise, novel ideas for intermediate layers, i.e., constructing the interconnecting layer to join perovskites and organic subcells, are emerging. Hence, this review revisits and gives insightful comments on these latest developments, highlighting the existing challenges and providing key research ideas for future research explorations.